The On-The-Job Training Experiences of Business Administration Students of Philippine Electronics and Communication Institute of Technology Butuan City - Hingpit, Sheigfred Paulo (JPAIR Multidisciplinary Research, 2024)
On-the-job training is a crucial component of business administration education that helps students develop practical skills and knowledge in real-world settings. To establish an effective OJT program, it must align with the goals of the business administration curriculum and the industry, while the policies must provide clear guidance on student selection, placement, and evaluation. However, OJT can be adversely affected by many socioeconomic factors. The study used experiential learning theory, a qualitative methodology using semi-structured interviews to explore the experiences of business administration students at the Philippine Electronics and Communication Institute of Technology in their on-the-job training. Study aimed to investigate the opportunity and challenges during the OJT, the coping mechanism of the interns, the monitoring strategies employed to oversee the interns, the assessment of BSBA interns to the Host Agencies/Industry/Supervisor, the assessment received of BSBA Students from the Host Agencies/Supervisor, and based on the findings of the study, what intervention program may be designedIn the study, the BSBA student interns experienced practical experience and basic office work in their OJT program. However, their experience in their OJT program is not significantly aligned with their course and the internship description. The student interns’ coping mechanisms include adaptation mechanisms and motivation. Monitoring strategies such as activity, compliance, and result monitoring were effective in monitoring the performance of student interns based on the feedback on the evaluation sheet provided by the institution to the host agencies.